1997
DOI: 10.1046/j.1469-8137.1997.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of symbiosis‐related polypeptides during the early stages of the establishment of arbuscular mycorrhiza between Glomus mosseae and Pisum sativum roots

Abstract: SUMMARYChanges in polypeptide contents following inoculation of roots of Pisum sativum L. (wild type cv. Frisson (myc^, nod^)) with the arbuscular mycorrhizal fungus Glomus mosseae were analysed by two-dimensional gel electrophoresis (2D-PAGE). A different polypeptide pattern was obtained in a mycorrhiza-resistant pea genotype P2 (myc", nod") inoculated with G. mosseae. In order further to characterize the polypeptide modifications detected and to provide evidence for some possible symbiosis-related (SR) prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 59 publications
2
21
1
2
Order By: Relevance
“…These data confirm those reported in tobacco (Dumas-Gaudot et al, 1994) and pea (Samra et al, 1997). In Ri-T-DNA transformed tomato root the accumulation of two new acidic polypeptides of 24 and 39 kDa has been reported (Simoneau et al, 1994) during the development of mycorrhiza ; however, we have not been able to detect these polypeptides.…”
Section: supporting
confidence: 62%
See 4 more Smart Citations
“…These data confirm those reported in tobacco (Dumas-Gaudot et al, 1994) and pea (Samra et al, 1997). In Ri-T-DNA transformed tomato root the accumulation of two new acidic polypeptides of 24 and 39 kDa has been reported (Simoneau et al, 1994) during the development of mycorrhiza ; however, we have not been able to detect these polypeptides.…”
Section: supporting
confidence: 62%
“…Our results concerning the effect of AM symbiosis on root gene expression, as with those reported by Dumas-Gaudot et al (1994) and Samra et al (1997), contrast with those obtained for ectomycorrhizas (Hilbert & Martin, 1988 ;Burgess et al, 1995). For the ectomycorrhizal associations studied, it has been shown that development of the symbiosis induced a massive decrease in the concentration of the proteins synthesized by the plant.…”
Section: contrasting
confidence: 57%
See 3 more Smart Citations